Children's solving of mathematical word problems: The contribution of working memory - Pavlin-Bernardić, Nina (Array, 2008)
The aim of this study was to examine the contribution of working memory to children’ s solving of change and compare word problems. First- to fourth-grade primary school students (N=283) participated in the study. Two working memory measures were used: backwards digit span and listening span. On the whole sample, both predictors significantly explained the achievement variance in compare problems. For change problems, the results were different for younger and older students. For first and second grade students the achievement in listening span task was a significant predictor of the achievement in change problems, while the achievement in backward digit span task was not a significant predictor. However, for third and fourth grade students, none of the predictors were significant. The results confirmed the assumptions of theories which emphasize the importance of linguistic factors in solving mathematical word problems.